2020
DOI: 10.1101/gr.266676.120
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing identifies multiple early introductions of SARS-CoV-2 to the New York City region

Abstract: Effective public response to a pandemic relies upon accurate measurement of the extent and dynamics of an outbreak. Viral genome sequencing has emerged as a powerful approach to link seemingly unrelated cases, and large-scale sequencing surveillance can inform on critical epidemiological parameters. Here, we report the analysis of 864 SARS-CoV-2 sequences from cases in the New York City metropolitan area during the COVID-19 outbreak in Spring 2020. The majority of cases had no recent travel history or known ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 35 publications
8
67
0
2
Order By: Relevance
“…By late February, wide-spread community transmission of SARS-CoV-2 in the U.S. was identified in Washington state 7 , New York City 8 , and Santa Clara County in California 9 , but it is estimated that local transmission in the U.S. started earlier and was more wide-spread than recognized at the time 10,11 . Elsewhere, outside of these early virus 'hotspots' in the U.S., transmission of SARS-CoV-2 occurred mostly silently due to lack of testing until the second week of March 10,12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…By late February, wide-spread community transmission of SARS-CoV-2 in the U.S. was identified in Washington state 7 , New York City 8 , and Santa Clara County in California 9 , but it is estimated that local transmission in the U.S. started earlier and was more wide-spread than recognized at the time 10,11 . Elsewhere, outside of these early virus 'hotspots' in the U.S., transmission of SARS-CoV-2 occurred mostly silently due to lack of testing until the second week of March 10,12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…NGS methods have been rapidly adapted to the SARS-CoV-2 paradigm and shown to be applicable to a wide variety of associated biological questions [ 35 , 69 , 82 , 88 , 90 , 93 , 99 ]. The rate of data production and analysis has been unprecedented and would have been inconceivable only a few years ago.…”
Section: Resultsmentioning
confidence: 99%
“…While one hand, Xiao et al . [ 87 ] found that hybrid capture sequencing is less sensitive than amplicon-based methods for the sequencing of SARS-CoV-2 genomes, and did not recommend its application for challenging samples with low viral loads, in other studies enrichment by hybridization has been successful even for samples with very low viral loads [ 93 ]. Capture-based methods may also offer unbiased representation of intra-sample variants.…”
Section: High-throughput Sequencing For Covid-19 Pandemicmentioning
confidence: 99%
“…Genomic evidence from early SARS-CoV-2 strains suggests that initial infections in the United States were introduced to Washington State, a hub for travel to East Asia, by travelers from China [ 18 - 20 ]. There is also evidence that suggests New York City likely served as a primary entry point to the United States for the SARS-CoV-2 contagion from European hotspots in Spain and Italy early in the pandemic [ 19 , 21 , 22 ]. Chicago, Boston, and Detroit were likely additional entry points because of the large number of international travelers—Detroit’s metro airport had over 1100 flights per day to 4 continents including direct flights to China and Europe [ 23 ], and was the least busy of the airports.…”
Section: Introductionmentioning
confidence: 99%